2014
DOI: 10.1785/0120130287
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude Limits of Subduction Zone Earthquakes

Abstract: Maximum earthquake magnitude (m x ) is a critical parameter in seismic hazard and risk analysis. However, some recent large earthquakes have shown that most of the existing methods for estimating m x are inadequate. Moreover, m x itself is ill-defined because its meaning largely depends on the context, and it usually cannot be inferred using existing data without associating it with a time interval. In this study, we use probable maximum earthquake magnitude within a time period of interest, m p T, to replace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 85 publications
1
53
0
Order By: Relevance
“…In global studies, Bird and Kagan (2004) found the m c of continental strike-slip faults to be 8:01 0:47 −0:21 and for subduction zones 9:58 0:48 −0:46 . Other estimates for subduction zones include m c 9 − 9:7 (Kagan and Jackson, 2013) and m p T ≥ 9, in which T 10;000 yrs (Rong et al, 2014).…”
Section: Uncertainties and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In global studies, Bird and Kagan (2004) found the m c of continental strike-slip faults to be 8:01 0:47 −0:21 and for subduction zones 9:58 0:48 −0:46 . Other estimates for subduction zones include m c 9 − 9:7 (Kagan and Jackson, 2013) and m p T ≥ 9, in which T 10;000 yrs (Rong et al, 2014).…”
Section: Uncertainties and Discussionmentioning
confidence: 99%
“…The largest recorded earthquake in instrumental records is the 1992 M w 7.1 Cape Mendocino event (Oppenheimer et al, 1993); there are very few other earthquakes here on record that were even medium-sized. In our analysis, we use a convergence rate of 40 5 mm=yr (Wilson, 1993;Wech and Creager, 2011) and a dip of 10° (Savage et al, 1991;Rong et al, 2014). The vertical extent of the seismogenic zone has been debated, from 15 km (Dragert et al, 1994) to 20-30 km (Williams et al, 2011;Hyndman, 2013;Rong et al, 2014); here we take a value of 25 10 km, giving an average seismogenic width of 125-150 km.…”
Section: Cascadia Subduction Zonementioning
confidence: 99%
See 2 more Smart Citations
“…Several models have been proposed to address the shortcomings of the GR recurrence law (Kagan, 1997(Kagan, , 2002aBird and Kagan, 2004). For SZs, such as the CSZ used as an example in this paper, a Tapered Gutenberg-Richter (TGR) distribution has been shown to be a robust model (Rong et al, 2014). The TGR is expressed as a function of the seismic moment M 0 , instead of magnitude m and an exponential taper is applied to the number of events with very large seismic moment.…”
Section: Earthquake Fault Source Models and Their Characteristicsmentioning
confidence: 99%